Podsumowanie i wnioski (Forms of Power in Contemporary World – Case Studies, 2023)
The Summary contains conclusions from the case studies presented in the book. The analysis of the potential and international strategies of selected countries shows that a world power must possess sufficient power resources in all key dimensions: economic, military and political. While some countries more or less successfully aspire to this status, others have settled for the rank of "middle power". Although middle power is not able to independently implement all the goals of its foreign policy, it at least has sufficient resources to effectively deter potential aggressors and lead in selected fields of international activity.